Penanaman Pendidikan Karakter Bercirikan Agama Buddha di Sekolah Buddhis - Praptiyono, Kabul; Singamurti, Mirrah megha (Sekolah Tinggi Teologi Injili dan Kejuruan (STTIK) Kupang, 2025)
This study aims to describe the implementation of character education based on Buddhist values in Buddhist schools. The research adopts a qualitative descriptive approach involving school principals, teachers, parents, and students as subjects. Data were collected through interviews and observations, and analyzed using the interactive model of Miles and Huberman, which includes data reduction, data display, and conclusion drawing. The results show that the implementation of character education in the school has been carried out optimally through the curriculum, habituation activities, collaboration among stakeholders, availability of facilities and infrastructure, and the role of educators. The character education based on Buddhist values refers to the three fundamental aspects of Buddhist religious education: Pariyatti (theoretical knowledge of the teachings), Patipatti (practical application), and Pativedha (realization or spiritual enlightenment). These three aspects serve as the foundation for shaping students’ character to be religious, tolerant, and morally upright.